Equilibrium, kernel, integration in the multiregional system under liberalization of external trade - Alexander Granberg; Victor Suslov; Larisa Melnikova (European Regional Science Association (ERSA), 1998)
The paper continues studies on the modeling of interregional systems of the USSR and Russia, presented at the previous congresses of the ERSA. Complex of multiregional models of optimization and equilibrium (30 sectors, 5 macroregions of Russia) is used. Effects of interregional interactions in Russian economy, economic equilibrium and the system kernel (multitude of mutually beneficial exchanges) are determined. The study is carried out for the three regimes of external trade: centralized trade (as in the USSR), limited liberalization of trade (customs regulation), complete liberalization of trade. Interpretation of actual dynamics and changes in the structure of the economy of the regions and interregional linkages is given. Impact of financial transfers "centre-regions" on the interregional integration and homogenity of economic space is assessed.
Keywords: 330